Bracelets with grammar school students in the role of religious and ethnical identity defining - Pavlović Aleksandar (Baština, 2010)
The author stresses the importance of bracelets carrying, which is, at the end of the first decade of the 21st century widely spread among the inhabitants of Serbia, and especially among youth. It is about bracelets made following the sample of the same prayer-ritual requisite being encountered in use with Orthodox personnel. The popularity of bracelets are observed by the author as a result of the process of retarditionalization, raised in Serbia at the end of the 80-ties and beginning of the 90-ties years of the 20th century, when religious tradition is being revitalized and influence of religious institutions is being renewed. Firstly in the field of politics, and then almost in all fields of social life, retarditionalization leads to the establishment of strong discourse in which nationalist rhetoric primarily supported by religious and ethnic elements is dominating. The author proceeds from the hypothesis that in ideo-symnbolic establishment, which has still been governing in Serbia twenty years from the beginning of the retarditionalization, where ethnic and religious discourse prevail, bracelets appear as a means of firstly religious and afterwards ethnic identity defining. The empiric material for the mentioned hypothesis check is collected at the sample of 40 grammar school students in Kosovska Mitrovica and Leposavić in the North of Kosovo and Metohia. The answers which are reached show that the interviewed recognize bracelets as things in accordance with some religious ideal, and beginning from then it is presented in their mind in accordance with adequate meanings. A great majority of the interviewed by mere fact it carries bracelet determines itself as the Orthodox (male or female), and almost two thirds at the same time as Serb (male of female). Finally, the author concludes bracelets could be observed as thing, that is, as the product which is in the function of the reproduction of the Orthodox ideology by its symbolism. The author considers furthermore that the initial hypothesis has got the confirmation in the comprehensions of the interviewed, and therefore interpretation of bracelets as a means in the definition of the religious together with ethnic identity has some justification. The attitudes elaborated are considered as the initial ones and only indicative, and in order to acquire more thorough knowledge he is pleading for more extensive researches undertaking on that matter.